2020
DOI: 10.1002/mgg3.1152
|View full text |Cite
|
Sign up to set email alerts
|

Novel KLHL26 variant associated with a familial case of Ebstein’s anomaly and left ventricular noncompaction

Abstract: Background: Ebstein's anomaly (EA) is a rare congenital heart disease of the tricuspid valve and right ventricle. Patients with EA often manifest with left ventricular noncompaction (LVNC), a cardiomyopathy. Despite implication of cardiac sarcomere genes in some cases, very little is understood regarding the genetic etiology of EA/LVNC. Our study describes a multigenerational family with at least 10 of 17 members affected by EA/LVNC. Methods: We performed echocardiography on all family members and conducted ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Mutations in Klhl26 (Kelch-like family member protein 26) have been associated with Ebstein’s anomaly. Patients manifest with left ventricular non-compaction [ 240 ]. In silico analysis suggests that this variant may disrupt the interaction with cullin-3, but functional analysis will be required to confirm its pathogenicity [ 240 ].…”
Section: The Roles Of Cullin-3 E3-ligase Complexes In Cardiac and mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in Klhl26 (Kelch-like family member protein 26) have been associated with Ebstein’s anomaly. Patients manifest with left ventricular non-compaction [ 240 ]. In silico analysis suggests that this variant may disrupt the interaction with cullin-3, but functional analysis will be required to confirm its pathogenicity [ 240 ].…”
Section: The Roles Of Cullin-3 E3-ligase Complexes In Cardiac and mentioning
confidence: 99%
“…Patients manifest with left ventricular non-compaction [ 240 ]. In silico analysis suggests that this variant may disrupt the interaction with cullin-3, but functional analysis will be required to confirm its pathogenicity [ 240 ]. Substrates of Klhl26 in cardiac cells are still unknown and muscle-specific functions for this cullin-3 substrate adapter protein await further characterization.…”
Section: The Roles Of Cullin-3 E3-ligase Complexes In Cardiac and mentioning
confidence: 99%
“…Increasing evidence has demonstrated that KLHL family members play a vital role in mammalian cardiac development and occurrence of myocardial disease. Mutations in KLHL26 cause malformations of cardiac development and function 15 . Inactivation of KLHL24 leads to the accumulation of desmin intermediate filaments, which causes the occurrence of hypertrophic cardiomyopathy (HCM) 16 .…”
Section: Discussionmentioning
confidence: 99%
“…All KLHL family members contain a highly conserved BTB/POZ domain, back domain, and six repeating Kelch motifs, in which BTB domain can bind with cullin3 (CUL3) to form an E3 ligase, recruit substrates for ubiquitination and degradation and play an essential role in post‐translational gene expression regulation via mediating many important physiological and pathological processes, including mitosis, embryonic development, inflammatory response, cell cycle regulation, and cell apoptosis 11–14 . In particular, resent studies found that aberrant expression of KLHL genes is highly associated with the occurrence and development of cardiovascular disease and has attracted wide attention 15–17 . Using database mining (https://www.ncbi.nlm.nih.gov/geo/) and analysis, KLHL38 may be a new potential target in the therapeutic of HF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation